ANALISIS KELAYAKAN FINANSIAL USAHA MEUBEL ROTAN PADA CV. BONE LAYANA JAYA DI KOTA PALU - Fadhilla, Nurul; Hadayani, Hadayani; Alam, Max Nur (AGROTEKBIS, 2017)
Rattan is one of the many forest products demand after wood. Central Sulawesi province is one ofthe areas producing rattan, rattan furniture industry ishighly prospective for developed in the city of Palu.One of the industries that manage rattan into various craft Rattan Furniture is on the CV. Bone Layana Jaya. The purpose of this research is to know the financial feasibility of rattan furniture onthe CV.Bone Layana Jaya in the city of Palu last five years from 2011-2015. The determination of the location is done deliberately (purposive) with the consideration that this industry is one of the rattan processing industry which is already developed and no one has researched this industry. The collection of data on this industry is the primary data and secondary data. The analysis used based on the criteria of Payback period (PP), Net Present Value (NPV), Benefit Cost Ratio (Net B/C Ratio) and Internal Rate of Return (IRR). Payback Period analysis results obtained have a refund for 1 year and 8 months stated feasible. Net Present Value is obtained after the discount factor with an interest rate of 36% per year accrued at Rp 90,436,634 and stated feasible because of (NPV>0). Net Benefit Cost Ratio are obtained of 1,74 and stated feasible because of (Net > B/C 1). Internal Rate of Return obtained of 39,8% >36% and stated feasible. Based on that results the rattan furniture at the CV. Bone Layana Jaya in the city of Palu were declared eligible to run.